Gamma‐Glutamyl Transpeptidase‐to‐Platelet ratio predicts liver fibrosis in patients with concomitant chronic hepatitis B and nonalcoholic fatty liver disease. Issue 8 (9th July 2022) - Luo, Jie; Du, Zhan; Liang, Dongli; Li, Manni; Yin, Yanyao; Chen, Mingfa; Yang, Liuqing
Abstract: Objectives: The aim of this study was to compare the correlation of gamma‐glutamyl transpeptidase‐to‐platelet ratio (GPR), aspartate aminotransferase‐to‐platelet ratio index (APRI), fibrosis index‐4 (FIB‐4), and liver stiffness measurement (LSM) in the diagnosis of liver fibrosis, and perform a diagnostic value of GPR for predicting fibrosis in CHB patients with NAFLD. Methods: A retrospective study was conducted on CHB patients concurrent with NAFLD between September 2019 and December 2020. They were divided into control group (LSM ≤ 9.7 kpa) and fibrosis group (LSM ≥ 9.8 kpa). Demographic data were collected; ALT, AST, and PLT were also detected. LSM was measured by transient elastography (TE). The GPR, APRI, and FIB‐4 were calculated. The correlation between GPR, APRI, FIB‐4, and LSM was compared. The accuracy of predicting liver fibrosis using GPR, APRI, and FIB‐4 was assessed. Results: Eighty‐five CHB patients with NAFLD were enrolled. Multivariate analysis showed that age ( p  = 0.005), GGT ( p  = 0.001), and PLT ( p  = 0.013) were the independent risk factors for LSM. The GPR ( p  = 0.008), APRI ( p  = 0.001), and FIB‐4 ( p  = 0.001) values in fibrosis group were higher than control group. Pearson linear correlation was used to analyze the correlations between LSM and GPR, APRI, and FIB‐4. LSM was correlated with GPR, APRI, and FIB‐4. The AUCs of GPR, APRI, and FIB4 were 0.805, 0.766, and 0.826 in assessing liver fibrosis, respectively. No significant differences in the areas of GPR were comparable to that of APRI and FIB‐4. Conclusion: GPR has a good correlation with LSM in assessing liver fibrosis and can be used as a noninvasive index for the assessment of liver fibrosis in patients with concomitant CHB and NAFLD. Abstract : The correlations between LSM and GPR, APRI, FIB‐4. (A) between LSM and GPR ( r  = 0.244, p  = 0.024), (B) between LSM and APRI ( r  = 0.344, p  = 0.001), (C) between LSM and FIB‐4 ( r  = 0.306, p  = 0.004). Abbreviations: APRI, aspartate aminotransferase‐to‐platelet ration index; FIB‐4, fibrosis‐4; GPR, gamma‐glutamyl transpeptidase ‐to‐platelet ration; LSM, liver stiffness measurement.ROC curves of GPR, APRI, and FIB‐4 for significant fibrosis assessment in CHB patients with NAFLD. (A) GPR (AUC = 0.806), (B) APRI (AUC = 0.767), (C) FIB‐4 (AUC = 0.826). Abbreviations: APRI, aspartate aminotransferase‐to‐platelet ration index; AUC, area under the ROC curve; FIB‐4, fibrosis‐4; GPR, gamma‐glutamyl transpeptidase ‐to‐platelet ration.